2022
DOI: 10.3390/ph15101225
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenols, Saponins and Phytosterols in Lentils and Their Health Benefits: An Overview

Abstract: The lentil (Lens culinaris L.) is one of the most important legumes (family, Fabaceae). It is a natural functional food rich in many bioactive compounds, such as polyphenols, saponins and phytosterols. Several studies have demonstrated that the consumption of lentils is potentially important in reducing the incidence of a number of chronic diseases, due to their bioactive compounds. The most common polyphenols in lentils include phenolic acids, flavan-3-ol, flavonols, anthocyanidins, proanthocyanidins or conde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 111 publications
1
19
0
1
Order By: Relevance
“…Saponins are amphiphilic glycosidic secondary metabolites produced by several plants that possess emulsifying and foaming properties [52]. Lentils are one of the main sources of saponins in the human diet [13]. According to our findings, the highest saponin level was displayed in brown lentils (0.03 ± 0.01 mg AE/g).…”
Section: Phenolic Compounds and Saponin Estimation (Tpc Tfc Ttc Tct T...mentioning
confidence: 63%
See 3 more Smart Citations
“…Saponins are amphiphilic glycosidic secondary metabolites produced by several plants that possess emulsifying and foaming properties [52]. Lentils are one of the main sources of saponins in the human diet [13]. According to our findings, the highest saponin level was displayed in brown lentils (0.03 ± 0.01 mg AE/g).…”
Section: Phenolic Compounds and Saponin Estimation (Tpc Tfc Ttc Tct T...mentioning
confidence: 63%
“…Most studies correlate phenolic compounds with their potential health benefits, including antioxidant capacity and other health-promoting properties [40]. According to a recent review of polyphenols in lentils [13], the most frequently found polyphenols in lentils comprise phenolic acids, flavonols, flavan-3-ol, proanthocyanidins, anthocyanidins, or condensed tannins, and anthocyanins. Therefore, this study intended to evaluate the TPC, TFC, TTC, TCT, TPAC, and TAC, besides the saponin estimation.…”
Section: Phenolic Compounds and Saponin Estimation (Tpc Tfc Ttc Tct T...mentioning
confidence: 99%
See 2 more Smart Citations
“…Les alcaloïdes sont connus pour leurs effets antipaludiques comme c'est le cas pour la quinine, molécule alcaloïdes extraite de l'écorce de Cinchona officinalis (Uzor, 2020). Les polyphénols ont des propriétés anticancérigènes, cardioprotectrices, antidiabétiques, antioxydantes et antiinflammatoires (Mitsunari et al, 2021 ;Mustafa et al, 2022 ;Yoshioka et al, 2022).La présence de ces constituants phytochimiques dans l'EAJG justifieraient les effets pharmacologiques de cette plante.…”
Section: Discussionunclassified